Identification and phylogenetic analysis of Aedes species (Diptera: Culicidae) and arboviruses associated with them across tropical and temperate regions of South Africa (2015-2018) - Venter, Marietjie (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2020.